THE EFFECT OF DIFFERENT NATURAL FEEDING ON THE GROWTH AND LIFE OF MALI LARVES (Labiobarbus festivus, Heckel 1843) - Sianipar, Doni MangasiPandapotan; Sukendi, Sukendi; Aryani, Netti (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2021)
ABSTRACT            Natural feeds that are often used as initial feed for fish larvae include Artemia nauplii, water fleas, earthworms, and Tubifex sp. Through adequate feeding, as well as high nutritional content, it can spur growth in Malian Fish. This study aims to determine the effect of different natural feeding on the growth and survival of the larvae of Mali (L. festivus). The method used was an experimental method using a completely randomized design (CRD) with 1 factor, 3 levels of treatment, and 3 replications. The treatments given were P1: Tubifex sp, P2: Water fleas, P3: Chlorella sp. The parameters measured were absolute weight growth, absolute length growth, daily weight growth rate, life span and water quality. The results showed that the best treatment for the effect of growth and survival of mali fish larvae (L. festivus) was natural food for Tubifex sp. The absolute weight growth is 0.24 grams, the absolute length growth is 2.57 cm, and the daily weight growth rate is 14.85%. Meanwhile, the best survival rates were obtained at Tubifex sp. amounted to 88.89%. Water quality parameters during the study temperature: 27-27.4 ° C, pH: 7.2-7.3, DO: 4.1-5.2 mg / L.           Keywords:natural feed, Mali fish, growth, absolute weights